Proceedings of the 20th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2014
DOI: 10.1145/2623330.2623705
|View full text |Cite
|
Sign up to set email alerts
|

Mobile app recommendations with security and privacy awareness

Abstract: With the rapid prevalence of smart mobile devices, the number of mobile Apps available has exploded over the past few years. To facilitate the choice of mobile Apps, existing mobile App recommender systems typically recommend popular mobile Apps to mobile users. However, mobile Apps are highly varied and often poorly understood, particularly for their activities and functions related to privacy and security. Therefore, more and more mobile users are reluctant to adopt mobile Apps due to the risk of privacy inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 20 publications
0
81
0
1
Order By: Relevance
“…Awareness mechanisms such as privacy "nudges" have also been found to be reasonably successful as a deterrent for some users [12]. Recommending mobile apps to users by providing information about the security and privacy aspects has also been suggested [13]. However, we found that most of the previous work in this area only looks at leakage of mobile data and not social media data which SMAs have access to as well.…”
Section: Analysis Of Mobile Data Access Permissionsmentioning
confidence: 97%
“…Awareness mechanisms such as privacy "nudges" have also been found to be reasonably successful as a deterrent for some users [12]. Recommending mobile apps to users by providing information about the security and privacy aspects has also been suggested [13]. However, we found that most of the previous work in this area only looks at leakage of mobile data and not social media data which SMAs have access to as well.…”
Section: Analysis Of Mobile Data Access Permissionsmentioning
confidence: 97%
“…So this type of fraud are detected using GPS traces collected from numerous of taxi's and from these GPS traces different evidences are collected and finally these evidences are merged using dempster-shafer theory. Maksims et al [3] solves Meta search and collaborative filtering problems mainly by using flexible probabilistic model over pearly comparisons, in which various preferences over objects must be aggregated into a consensus ranking. Jeevanandam et al [4] introduces Opinion mining using Learning Vector Quantization classifier.…”
Section: IImentioning
confidence: 99%
“…There are many apps supporting many operating system such as android and Mac. As apps are growing daily and many new apps are launched everyday so it gets difficult for viewer to select the best apps,so many App stores launches daily App leader boards, which shows the rankings of various popular Apps [1,3]. The App leader board is one of the most important ways for detecting weather that app is true or not.…”
Section: Introductionmentioning
confidence: 99%
“…If an app is used to store student data (e.g., grades, contact information, or demographic information), ensuring the data stored is secure and is not accessible to unauthorized users is crucial (Zhu et al, 2014). A common method to secure the data stored in an app is to include an additional authorization procedure by requiring a passcode to execute an app.…”
Section: B6 Securitymentioning
confidence: 99%